Uganda : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2010)
This Joint Staff Advisory Note reviews the National Development Plan (NDP) 2010/11 to 2014/15 prepared by the government of Uganda. The NDP is the first in a series of six plans intended to move the country toward the national vision of a transformed modern economy in the next 30 years. The NDP expands on the vision of the earlier Poverty Eradication Action Plans, and was developed through an extensive and broad-based country-driven consultative process over the period 2008-09. IMF staff has recommended some measures to strengthen the NDP and enhance its implementation.